Higher anthocyanin intake is associated with a lower risk of non-alcoholic fatty liver disease in the United States adult population - Xiang, Shuai; Li, Yujing; Li, Ying; Pan, Wenjun; Wang, Xiaoqian; Lu, Yun; Liu, Shanglong (Frontiers in Nutrition, 2023)
Abstract Background: Flavonoids are a class of plant chemicals known to have health-promoting properties, including six subclasses. Anthocyanin is one of the subclasses that have anti-inflammatory and antioxidant activities. However, the relationship between flavonoid subclass intake and the risk of non-alcoholic fatty liver disease (NAFLD) and liver fibrosis has not been verified in representative samples of the United States. Methods: This is a cross-sectional study based on the data from the National Health and Nutrition Examination Survey (NHANES) and the Food and Nutrient Database for Dietary Studies (FNDDS) in 2017-2018. The intake of flavonoid subclasses of the participants was obtained from two 24-hour dietary recalls. The NAFLD and liver fibrosis were defined based on the international consensus criteria. The relationship between flavonoid subclass intake and NAFLD and liver fibrosis was evaluated using a multivariate logistic regression model corrected for multiple confounding factors. Subgroup analysis, trend tests, interaction tests and restricted cubic spline were carried out to further explore this relationship. In addition, we also explored the relationship between anthocyanin and liver serum biomarkers, dietary total energy intake and healthy eating index (HEI)-2015 scores. Results: A total of 2,288 participants were included in the analysis. The intake of anthocyanin was significantly negatively associated with the risk of NAFLD, but not other flavonoid subclasses. A higher anthocyanin intake was significantly associated with a lower risk of NAFLD (quartile 4, OR 0.470, 95% CI 0.275–0.803). The results of subgroup analysis showed that the protective effect of dietary anthocyanin intake on NAFLD was more pronounced in participants of non-Hispanic whites, with hypertension and without diabetes (P for interaction <0.05). Alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), dietary total energy intake was significantly negatively correlated with dietary anthocyanin intake. We did not find any protective effect of flavonoid subclass intake on liver fibrosis. Conclusions: Anthocyanin, but not other flavonoid subclasses, can significantly reduce the risk of NAFLD. The protective effect was more pronounced in non-Hispanic whites, participants without diabetes and those with hypertension. Our study provides new evidence that anthocyanin intake has a reverse significant association with the risk for NAFLD.